Risk factors for COVID-19 among persons with substance use disorder (PWSUD) with hospital visits – United States, April 2020–December 2020. (1st March 2022) - Board, Amy R.; Kim, Sunkyung; Park, Joohyun; Schieber, Lyna; Miller, Gabrielle F.; Pike, Jamison; Cremer, Laura J.; Asher, Alice
Abstract: Introduction: Sociodemographic factors and chronic conditions associated with coronavirus disease 2019 (COVID-19) among persons with substance use disorder (PWSUD) are not well understood. We identified risk factors associated with COVID-19 among PWSUD with hospital visits. Methods: Using the Premier Healthcare Database Special COVID-19 Release, we conducted a case-control study using ICD-10-CM codes to identify PWSUD aged 12 years and older with hospital visits for any reason during April–December 2020. Multivariable logistic regression was used to calculate adjusted odds ratios (aOR) and 95% confidence intervals (CI) to identify factors associated with COVID-19 diagnosis among PWSUD (age, sex, race/ethnicity, U.S. Census Region, urban/rural classification, insurance payor type, comorbidities, and substance use disorder [SUD] type), and then stratified by SUD type. Results: From April-December 2020, 18, 298 (1.3%) of 1, 429, 154 persons with SUD in the database had a COVID-19 diagnosis. Among PWSUD, opioid use disorder (OUD; aOR = 1.24, 95% CI = 1.18–1.32), alcohol use disorder (AUD; aOR = 1.16, 95% CI = 1.11–1.22), cocaine or other stimulant use disorder (COUD; aOR = 1.28, 95% CI = 1.22–1.34), and multiple SUDs (aOR = 1.20, 95% CI = 1.15–1.26) were associated with higher odds of COVID-19, as were comorbidities such as chronic lower respiratory disease (aOR = 1.32, 95% CI = 1.26–1.37), chronic hepatitis (aOR = 1.45, 95% CI = 1.34–1.57), and diabetes (aOR = 1.78, 95% CI = 1.71–1.86). Conclusions: Among a sample of PWSUD, OUD, AUD, COUD, multiple SUDs, and associated comorbidities were associated with COVID-19 diagnosis. Integration of COVID-related care, care of other comorbidities, and SUD treatment may benefit PWSUD. Future studies are needed to better understand COVID-19 prevention in this population and to reduce disparities among subpopulations at increased risk. Highlights: Among PWSUD, males were more likely to have COVID-19. Racial and ethnic minority groups had higher odds of COVID-19 among PWSUD. Having a comorbidity increased likelihood of COVID-19 among PWSUD. Likelihood of a COVID-19 diagnosis differed by substance use disorder type.